Semiotika Roland Barthes pada Poster Film Budi Pekerti (2023) - Sari, Helga Pratama (MIMESIS, 2024)
Semiotics studies exist as a reading of the existence of signifier and signified which are currently called signs. Barthes in his method divides the significance of meaning into three stages, namely the denotation stage, the connotation stage, and the myth. These signs also can be found in film posters. The film poster that will be discussed in this research is Budi Pekerti (2023), directed and written by Wregas Bhanuteja. This research uses qualitative research methods. Qualitative methods aim to understand social phenomena seen from the participant’s perspective. The signifier and signified present in the Budi Pekerti film poster certainly produce connotation and denotation meanings that are in line with Barthes’s thinking.